Hershkovitzia (Diptera: Nycteribiidae): revision, phylogeny, and cophylogeny - Hrycyna, Gabriela; Graciolli, Gustavo (Zootaxa, 2023)
Hershkovitzia Guimarães & D’Andretta, 1956 belongs to Nycteribiidae (Diptera), a family of hematophagous and obligate ectoparasites of bats. Hershkovitzia parasitize bats in the Thyropteridae family, which includes only one genus, Thyroptera Spix, 1823. Hershkovitzia species mostly have a one-to-one association pattern with their hosts, except for H. cabala Peterson & Lacey, 1985 and Hershkovitzia autinoae sp. nov., which share the same host. A review is presented of the species known to date, i.e., H. primitiva Guimarães & D’Andretta, 1956, H. coeca Theodor, 1967, H. inaequalis Theodor, 1967, H. cabala, and H. mariae Hrycyna, Santos, Rêbelo & Graciolli, 2022, and a new species, H. autinoae sp. nov., is described herein. A parsimony analysis of Hershkovitzia was carried out based on a matrix of morphological characters. A cophylogenetic analysis of these parasites and their hosts was performed using a phylogeny of Thyroptera based on a modified version of a previously-published character matrix. As a result, both Hershkovitzia and Thyroptera are monophyletic. Hershkovitzia was divided and organized into two morphological groups based on its phylogeny. As the host of H. coeca is not known, five hypothetical coevolutionary scenarios were performed with each species of Thyroptera. For each coevolutionary scenario only one solution was generated, and all scenarios indicate that the hypothetical ancestor of Hershkovitzia emerged together with the hypothetical ancestor of Thyroptera. An identification key to Hershkovitzia species is presented together with schematic drawings of the abdomen, head, and legs of each species.